The time course changes in selected fatigue indicators in moderately trained participants - Maduna, Bongani Cyprian (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2019)
Background: During daily physical activities, individuals will encounter some level of fatigue. This is especially true for athletes who exert their bodies to achieve superior performance and attempt to delay the onset of fatigue as far as possible. However, fatigue is a progressive process that is part of physical exercise. It is therefore, important to understand the various factors associated with fatigue. Objective: The purpose of this research project was to observe the changes in perceptual, physiological responses, and workload while participants performed a fatiguing cycling exercise task. In order to observe the aforementioned changes, one of the three variables, either perceptual, physiological responses or workload was kept constant, while the other two were observed as dependent variables. There were three test conditions, which permitted each variable to be kept constant in at least one of the three test conditions. Methods: Thirty-six apparently healthy university students were recruited for the study. The exercise was of 35 minute duration for each condition, with the data collection for HR (physiological response), RPE (perceptual response), and power output (workload) occurring at two minute intervals from the eighth minute until the thirtieth minute. The participants were required to perform a peak-power-output test in order set the relative performance ranges for each participant in order to elicit an observable fatigue response from all the participants. The three conditions included constant HR response, constant workload, and constant RPE response where each participant performed all of the above conditions on separate days.Results: The perceptual (RPE) response increased significantly (p<0.05) over time in all three test conditions, even under the constant RPE condition where it was expected to remain unchanged throughout the test duration. The HR response only demonstrated a significant (p<0.05) increase over time under the constant workload condition. Lastly, workload remained constant in all three testing conditions. Conclusion: Participants may be able to exercise for longer periods during sub-maximal exercise if they disregard the RPE warning response. In the current study, the RPE response illustrated that participants were being exerted more over time; however, the participants still had physiological and workload capacity to continue exercising. This research project has confirmed the fact that fatigue is a multifaceted phenomenon. Furthermore, it has been illustrated that RPE response alone as an indicator of fatigue onset may be misleading as participants did not breach the HR and workload steady state during the current research. Therefore, it may be more appropriate to assess fatigue onset through the assessment of more than one fatigue variable in order to ensure increased accuracy of the participants' fatigue state assessment.
Keywords: Athletes -- Health and hygiene; Fatigue; Athletes -- Physiology